A scientometric analysis approach on the plastic sand. Issue 3 (March 2023) - Iftikhar, Bawar; Alih, Sophia C.; Vafaei, Mohammadreza; Alrowais, Raid; Bashir, Muhammad Tariq; Khalil, Alamgir; Rizwan, Muhammad; Javed, Muhammad Faisal; Rehman, Muhammad Faisal; Mohamed, Abdullah
Abstract: The purpose of this research was to conduct a scientometric evaluation of the literature pertaining to plastic sand in order to evaluate its many aspects. Conventional review studies have several limitations when it comes to their capacity to completely and properly link different sections of the published research. Some of the more complicated features of advanced research are co-occurrence analysis, science mapping and co-citation analysis. During the study, the most inventive authors/researchers renowned for citations, the sources with the largest number of publications, the actively involved domains, and co-occurrences of keywords in the research on plastic sand are investigated. This study is limited to scientometric analysis of the available literature data on plastic sand. The VOSviewer application (version 1.6.18) was used to perform the analysis after bibliometric data for 4512 publications were extracted from the Scopus database and utilised in the extraction process from the year 2021 to June 2022. With the support of a statistical and graphical description of researchers and nations that are contributing, this study will aid researchers in the establishment of collaborative ventures and the exchange of fresh techniques and ideas with one another.